Unusual Presentation of Neurocysticercosis: Report of Two Cases - Gurung, Ghanashyam; Shrestha, Bhiva; Shah, Tilak C.; Pokhrel, Laxman R.; Sayami, Geeta; Shilpakar, Sushil K. (Nepal Journal of Neuroscience, 2005)
Neurocysticercosis (NCC) is the most common parasitic infestation of the central nervous system, and is one of the major public health problems in developing nations like Nepal. On imaging studies, NCC usually demonstrates multiple parenchymal ring enhancing lesions in the gray white matter interface of the brain, though presence of nonenhancing vesicles with scolex or calcified dots is also a frequent finding. Co-existence of brain abscess and neurocysticercosis is a rarity. Presentation of NCC in the form of a large cystic mass in the 4th ventricle is also unusual. Here, we present these unusual cases of neurocysticercosis, which remained in their masks until they were surgically explored and microscopically unveiled! Nepal Journal of Neuroscience, Volume 2, Number 1, 2005, Page: 85-89